Development of a population pharmacokinetics and pharmacodynamics model of glucarpidase rescue treatment after high-dose methotrexate therapy - Fukaya, Yutaka; Kimura, Toshimi; Hamada, Yukihiro; Yoshimura, Kenichi; Hiraga, Hiroaki; Yuza, Yuki; Ogawa, Atsushi; Hara, Junichi; Koh, Katsuyoshi; Kikuta, Atsushi; Koga, Yuhki; Kawamoto, Hiroshi (Frontiers in Oncology, 2023)
Glucarpidase (CPG2) reduces the lethal toxicity of methotrexate (MTX) by rapid degradation. In this study, CPG2 population pharmacokinetics (popPK) analysis in healthy volunteers (phase 1 study) and popPK-pharmacodynamics (popPK-PD) analysis in patients (phase 2 study, n = 15) who received 50 U/kg of CPG2 rescue for delayed MTX excretion were conducted. In the phase 2 study, the first CPG2 treatment at a dose of 50 U/kg was intravenously administered for 5 min within 12 h after the first confirmation of delayed MTX excretion. The second dose of CPG2, with a plasma MTX concentration > 1 μmol/L, was administered to the patient more than 46 h after the start of CPG2 administration. The population mean PK parameters (95% CI) of MTX, obtained from the final model post hoc, were estimated as follows: CLrMTX = 2.424 L/h (95% CI: 1.755–3.093), VcMTX = 12.6 L (95% CI: 10.8–14.3), VpMTX = 2.15 L (95% CI:1.60–2.70), and α = 8.131 × 10^5 (4.864 × 10^5–11.398 × 10^5). The final model, including covariates, was CLrMTX (L/h): 3.248 × Body Weight / Serum creatinine / 60 (CV 33.5 %), VcMTX (L): 0.386 × Body Weight / body surface area (CV 29.1 %), VpMTX (L):3.052 × Body Weight / 60 (CV 90.6 %), and α (L/h): 6.545 × 10^5 (CV 79.8 %). These results suggest that the pre-CPG2 dose and 24 h after CPG2 dosing were the most important sampling points in the Bayesian estimation of plasma MTX concentration prediction at 48 h. This CPG2-MTX popPK analysis and Bayesian estimation of rebound in plasma MTX concentrations is clinically important to estimate > 1.0 μmol/L 48 h after the first CPG2 dosing. Clinical Trial registration: JMA-IIA00078 and JMA-IIA00097.